miR-218 inhibits the migration and invasion of glioma U87 cells through the Slit2-Robo1 pathway - GU, JIAN-JUN (Oncol Lett, 2015)
Malignant gliomas are the most common primary brain tumors in adults and are associated with the highest mortality rate. Glioma invasion is one of the most notable causes of the poor prognosis of this cancer. Preventing the invasive behavior of malignant glioma cells by altering effector molecules can significantly improve the prognosis of a patient. microRNAs (miRNAs) are small noncoding RNAs, ~22 nucleotides in length, that are able to function as oncogenes or tumor suppressors in human cancer. In the present study, the expression level of miRNA 218 (miR-218) was found to be markedly downregulated in glioma cell lines and human primary glioma tissues. miR-218 upregulation was found to dramatically reduce the migratory speed and invasive ability of glioma cells. Furthermore, it was demonstrated that ectopic expression of miR-218 in glioma cells resulted in the downregulation of roundabout, axon guidance receptor, homolog 1 (Robo1), upregulation of Slit homolog 2 (Slit2) and the expression of associated proteins following Robo1 knockdown by small interfering RNA. In addition, it was demonstrated that miR-218 inactivated the Slit2-Robo1 pathway through downregulating Robo1 expression by directly targeting the 3′-untranslated region (3′-UTR) of Robo1. The present results indicate that miR-218 plays important roles in preventing the invasiveness of glioma cells, and reveals a novel mechanism of miRNA-mediated direct suppression of the Slit2-Robo1 pathway in glioma.